2008
DOI: 10.1126/science.1148861
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Y Chromosomes Harbor Cryptic Variation with Manifold Functional Consequences

Abstract: The paucity of polymorphisms in single-copy genes on the Y chromosome of Drosophila contrasts with data indicating that this chromosome has polymorphic phenotypic effects on sex ratio, temperature sensitivity, behavior, and fitness. We show that the Y chromosome of D. melanogaster harbors substantial genetic diversity in the form of polymorphisms for genetic elements that differentially affect the expression of hundreds of X-linked and autosomal genes. The affected genes are more highly expressed in males, mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
292
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(305 citation statements)
references
References 27 publications
13
292
0
Order By: Relevance
“…Genome-wide gene expression in genotypes differing only in Y chromosome origin revealed cryptic Y chromosome diversity (Lemos et al, 2008;Lemos et al, 2010;Jiang et al, 2010;Branco et al, 2013a). These include changes in the expression level of genes involved with functions as varied as metabolism, cell division, immune response and chromatin structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Genome-wide gene expression in genotypes differing only in Y chromosome origin revealed cryptic Y chromosome diversity (Lemos et al, 2008;Lemos et al, 2010;Jiang et al, 2010;Branco et al, 2013a). These include changes in the expression level of genes involved with functions as varied as metabolism, cell division, immune response and chromatin structure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these studies support the expectation that Y-linked variation preferentially affects genes with male-biased expression and modifies male fertility. Interestingly, YRV affects genes with greater expression divergence between D. melanogaster and D. simulans and higher level of expression polymorphism within species (Lemos et al, 2008;Sackton et al, 2011). It is reasonable to expect that YRV will modulate the evolution of fast-evolving genes and contribute to speciation and hybrid incompatibility in Drosophila.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While Drosophila melanogaster has only 10-20 protein-coding loci on the Y chromosome, Lemos et al (2008) reported that it harbours substantial polymorphic regulatory variation that affects hundreds of X linked and autosomal loci with important functions.…”
Section: W and Y Chromosomesmentioning
confidence: 99%